7m-4+m=5-2(m+4)

Simple and best practice solution for 7m-4+m=5-2(m+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7m-4+m=5-2(m+4) equation:


Simplifying
7m + -4 + m = 5 + -2(m + 4)

Reorder the terms:
-4 + 7m + m = 5 + -2(m + 4)

Combine like terms: 7m + m = 8m
-4 + 8m = 5 + -2(m + 4)

Reorder the terms:
-4 + 8m = 5 + -2(4 + m)
-4 + 8m = 5 + (4 * -2 + m * -2)
-4 + 8m = 5 + (-8 + -2m)

Combine like terms: 5 + -8 = -3
-4 + 8m = -3 + -2m

Solving
-4 + 8m = -3 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
-4 + 8m + 2m = -3 + -2m + 2m

Combine like terms: 8m + 2m = 10m
-4 + 10m = -3 + -2m + 2m

Combine like terms: -2m + 2m = 0
-4 + 10m = -3 + 0
-4 + 10m = -3

Add '4' to each side of the equation.
-4 + 4 + 10m = -3 + 4

Combine like terms: -4 + 4 = 0
0 + 10m = -3 + 4
10m = -3 + 4

Combine like terms: -3 + 4 = 1
10m = 1

Divide each side by '10'.
m = 0.1

Simplifying
m = 0.1

See similar equations:

| 4xyz+5xyz= | | 2p^2=-44 | | 15=2y-4 | | x+8=2x-9 | | -7(3x-6)=210 | | 9x^3-18x^2-69x-3=0 | | -7(-3+7x)=-273 | | =n^2+9n+18 | | 0=1.1y+2.2 | | [x+3.5]=2.5 | | 3+65x-39x=39x+21 | | -2(x-1)=-2x+5 | | 9x^3-45x^2+72x-45=0 | | 1/4(a+7)=8 | | n-9j-7-4n-5j-7= | | 6x+6=-60-5x | | -8(-3n-3)=-8(-4n-8) | | 6(x+24)=2(x+30) | | -24=2x-14 | | =3k^2-33k+72 | | 4k+21=-5 | | 25-3x=10-8x | | 8=z/3+16 | | -2(4-3b)=-8(-b+4) | | 3k^2+73=33k | | -1+3x=-13x | | 2y(4)= | | -8x+2= | | -10q+5y+6-2q-y-6= | | -3(b+7)=6(b+4) | | 0=3x^2-6x+5 | | =(n+2)(2n+5) |

Equations solver categories